Negative c -axis longitudinal magnetoresistance in FeSe - Amigó, María Lourdes (2024)
Below the structural transition occurring at Ts=90K, FeSe exhibits positive transverse magnetoresistance when the current is applied parallel to the ab plane. In this study, we show that, in contrast, when both themagnetic field and the current are aligned along the c axis, the magnetotransport changes significantly. In this configuration, FeSe develops a sizable negative longitudinal magnetoresistance (∼15% at T=10K and μ0H=16T) in the nematic phase. We attribute this finding to the effect of the applied magnetic field on the scattering from spin fluctuations. Our observations reflect the intricate interplay between spin and orbital degrees of freedom in the nematic phase of FeSe.